Media Pembelajaran Berbasis Kinect Untuk Anak Berkebutuhan Khusus Autis Bertema Pengalaman Bersama Teman(Studi Kasus : Rumah Pintar Abk Kabupaten Salatiga) - Prahastiwi, Anindiya; , Fatah Yasin Al Irsyadi, S.T., M.T (2017)
Autistic children usually indicated by an interruption in communication. When teaching and learning process, the teachers are required to be creative in providing the materials due to the nature of the children who get bored quickly, so that the media needed to entice them to learn, play and can improve their ability, one using the game. The researchers make this games for giving the other alternatives of teaching and learning process by the teachers. The games created based on Autistic Student Book Themes 5 "Experiences with Friends", so objects that are used in this game they typically have a look at play, such as cycling, congklak, balls and the others. First of the researches is observation a conditions of the students, who is pointment actors of the games. Then, the researchers was conducted an interviews to the teachers for knowing a student capabilities and using curicullum for teaching and learning process. Unity game development utilizing software powered with Kinect technology. Implementation of this game for autistic students elementary schools 2nd grade in Rumah Pintar ABK Kabupaten Salatiga. The results of test, this game can be the one of a learning media can attracting of a student enthuasiastics for learn in fun away, because this game requires actives participation of users, by moving one of their hands while playing.